Pemanfaatan Kolam Tampung Sebagai Upaya Mitigasi Banjir Kawasan Pada Sub Sistem Medokan Ayu Kota Surabaya - Hafiizh Muhammad Imaaduddiin; Kuntjoro Kuntjoro; Ismail Sa'ud; Didik Harijanto; Dwi Indriyani (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2022)
Medokan Ayu is an area from Surabaya Drainage Master Plan 2018-2038, located in Rayon Jambangan and reported to be inundated. This caused by overcapacity of the existing drainage channel to accommodate the 2-year flood discharge. From 134 channels observed, 27 channels overflowed, and 20 out of 27 canals are located in residential areas so the inundation hampered the local citizens activities. For a discharge period of 10 years, overflow occurs in the upstream and the middle of the main channel due to the slope of the channel is too flat. Since it is not possible to change the base elevation upstream or downstream, a reservoir was created as a solution by utilizing the government's inventory area located near the downstream of the channel. This reservoir will have pump that stream the water back to downstream channel. So, with this flood control system, Medokan Ayu area can be free from inundation.